OSTROGIANA IN THE MENTAL DIMENSION OF IVAN OGIENKO (METROPOLITAN ILARION) - TYURMENKO, Iryna (HUMANITARIAN STUDIES: HISTORY AND PEDAGOGY, 2021)
The proposed publication includes the basic concepts and conclusions of the report delivered at the VII Ostroh Scientific Readings (September 27-28, 2019), organized by The Ostroh Academy Research Center of Inheritance Studies in order to study the princes’ of Ostroh heritage. The article reveals the influence of Ostroh and Ostrogiana on the life and work of Ivan Ogienko (known as Metropolitan Illarion). Having preserved Ostrogiana in the Ukrainian cultural heritage, the scholar noted that it played an important role in the life not only of Ukraine, but also of all Eastern Slavs. This idea was first expressed by the scientist in the course of lectures known as "Ukrainian Culture" (1918). Ostrogiana's subject matter accompanied the scientist throughout all his life, which is reflected in a number of his scientific works. At the same time, I. Ogienko's scientific experiments in this area divided modern scientists into those who sharply criticize I. Ogienko's views, and those who are in solidarity with the scientist and those who, in their pursuit of finding the truth, discuss and verify, the opinions and hypotheses expressed by I. Ogienko on the various problems of Ostrogiana. The article deals with the main markers that determined the direction of the scientist’s research: Ostrog, Ostroh Bible, printing, old prints, the figures of the Ostroh family. On the basis of comparative analysis, the relevance in the modern scientific space of ideas, the views of the scientist on the problems of Ostrogiana were determined. It has been emphasized that the scholar's views on the significance of the Ostroh Bible, the prominent role of I. Fedorov in the development of printing and in the publication of the Bible, the presence of various sources that formed the basis of the Bible translation, the high technical condition of printing and the specific features of Ostroh font; as well as on the Ostroh Cultural Center, which included the Ostroh Academy, a circle of scientists and a printing house; the date of death and burial of V.K. Ostroz’kyyi. The scholar emphasized that the translation of the Bible was based on the Church Slavonic language tradition and identified the reasons that hindered the translation of the Bible into a living language; proved that Ostroh printing house became the first permanent printing house in the Ukrainian lands; put forward a hypothesis about V.K.Ostroz’kyyi’s desire to transfer the cultural and educational center from Ostroh to Derman; on the basis of a comparison of fonts, he suggested that at the end of 1602 or the beginning of 1603 the Ostroh printing house was temporarily transferred to Derm. Considering Ostrog as the center of cultural heritage, the scientist combined its achievements with modern Ukrainian history, leaving for the future generations to solve the problems that he could not solve himself.